Dampak Perdagangan Bebas AFTA Terhadap Transformasi Ekonomi Indonesia - Salsa Rayhanis; Ayu Crisela; Mohammad Zein Saleh (JURNAL RISET MANAJEMEN (JURMA), 2024)
Free trade plays a crucial role in global economic development, especially in the era of globalization, and the ASEAN Free Trade Area (AFTA) aims to create a single market within the ASEAN region through the liberalization of trade in goods. This study examines the impact of AFTA on Indonesia's economic transformation, including increased export and import volumes as well as regional economic integration, highlighting benefits such as the growth of exports in manufacturing, agriculture, and consumer goods, alongside strengthening domestic industries. However, free trade poses risks, such as competition from imported products that could pressure local producers. Using a qualitative approach through literature studies, the findings show a significant increase in export and import volumes following AFTA implementation, although regional development disparities remain a challenge. This study emphasizes the need for strategies to improve product quality, enhance infrastructure, and build sectoral synergy to ensure inclusive economic integration and drive Indonesia's overall economic progress.